THE IMPORTANCE OF VOLLEYBALL GAME IN PHYSICAL EDUCATION LESSONS AT GYMNASIUM LEVEL - Ioan Sabin SOPA; Marcel POMOHACI (Editura Universităţii din Oradea, 2020)
Volleyball game can be a method for fulfilling the objectives of the physical education lesson, being fun and also doesn't require many materials and space. Our research studied the influence of volleyball game on a grup of 25 girls with age between 13-14 years from a gymnasium school. The methods used were experimental using some specific volleyball test like anthropometric measurments, speed running, endurance running, long jump, flexibility, abdominal strength, triple jump, 6 m x 5 m running. The results showed good improvements in every assessment comparing the results between the initial and final evaluation. Conclusions highlighted the idea that volleyball game can be a good method for fulfilling the objectives of every physical education class and also improve motor qualities and develop skills.